Transaksi Derivatif Lindung Nilai (Hedging) Pada Perusahaan Manufaktur (Studi Kasus PT Japfa Comfeed Indonesia Tbk Dan PT Hanjaya Mandala Sampoerna Tbk) - Alvi Nabilah; Salsabilla Ronardi; Queen Shakira Azzahra; Fitrah Maharani; Siti Rodiah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The purpose of this study to determine the application of hedging derivative transactions in manufacturing companies in indonesia. This study uses a qualitative approach with content analysis. This study uses annual reports for 2022. The results show that PT Japfa Comfeed Indonesia Tbk and PT Hanjaya Mandala Sampoerna Tbk, two of manufacturing companies use derivative instruments for hedging. The derivative transactions is include swaps, forward contracts, and options. In addition, manufacturing companies also use derivative instruments as risk mitigation. The company is conducting a large-scale business that allows the use of derivative instruments. Large-scale companies such as manufacturing companies usually have more funds to cover costs and consider the economic benefits of using derivatives which are considered variable costs.